Web development with jQuery - York, Richard (Wrox, a Wiley brand, 2015)
Newly revised and updated resource on jQuery's many features and advantages Web Development with jQuery offers a major update to the popular Beginning JavaScript and CSS Development with jQuery from 2009. More than half of the content is new or updated, and reflects recent innovations with regard to mobile applications, jQuery mobile, and the spectrum of associated plugins. Readers can expect thorough revisions with expanded coverage of events, CSS, AJAX, animation, and drag and drop. New chapters bring developers up to date on popular features like jQuery UI, navigation, tables, interacti.- Resumé vydavatel
Includes index.
Keywords: dotazovací jazyky; JavaScript (programovací jazyk); jQuery (knihovna-software); query languages; JavaScript (programming language); jQuery (library-software); elektronické knihy; příručky; electronic books; handbooks and manuals